2010
DOI: 10.1038/jid.2009.338
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation between the Molecular Subtype of COL1A1–PDGFB Fusion Gene and the Clinico-Histopathological Features of Dermatofibrosarcoma Protuberans

Abstract: Abbreviations: COL1A1, collagen type I-a 1; DFSP, dermatofibrosarcoma protuberans; PDGFB, plateletderived growth factor-B chain 904

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…This finding has been observed in previous studies [17,19,21,26]. Abbott el al [19] studied 10 DFSPs with fibrosarcomatous transformation (DFSP-FS) and compared FS areas with DFSP areas.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding has been observed in previous studies [17,19,21,26]. Abbott el al [19] studied 10 DFSPs with fibrosarcomatous transformation (DFSP-FS) and compared FS areas with DFSP areas.…”
Section: Discussionsupporting
confidence: 63%
“…The detection of the fusion gene COL1A1/PDGFB by RT-PCR is difficult due to the presence of multiple breakpoints of the gene COL1A1 and the problem of extracting RNA from paraffin-embedded tissue. In a recent study, from a series of 172 DFSP (137 already published), no association between the COL1A1 breakpoint position and clinicohistologic parameters was found [26]. The authors concluded that the simpler FISH analysis might appear to be a more appropriate method for routine detection of COL1A1/ PDGFB rearrangement in DFSP.…”
Section: Discussionmentioning
confidence: 93%
“…We characterized 20 distinct breakpoints in COL1A1, with a tendency for the breakpoint to occur in exons located in the second half of COl1A1. Nevertheless, as reported by our group and others, [19][20][21]37,38 there is no association between the presence of different breakpoints and the histologic variants of DFSP or their clinical characteristics.…”
Section: Discussionsupporting
confidence: 46%
“…RT-PCR has been the procedure most extensively reported. Using this technique, a constant involvement of exon 2 of PDGFB has been detected, whereas COL1A1 breakpoints occur in a wide variety of positions within the gene (Giacchero et al, 2010). In our previous experience (Llombart et al, accepted for publication), we observed that 76% is detected using RT-PCR in paraffin embedded tissue samples.…”
Section: Introductionmentioning
confidence: 88%
“…Exon 46 was the most frequently involved, followed by exons 25, 26, and 43. In a recent review of 172 cases compiled from different studies, Giacchero et al (2010) classified the implicated exons in four groups due to the high variability of the exons involved, but did not find any correlation between the molecular subtype of COL1A1/ PDGFB fusion gene and the clinicohistopathological features of the evaluated DFSP. We have also classified the exons into two different groups and reached the same conclusion.…”
Section: Comparison Between Rt-pcr and Fish Techniquesmentioning
confidence: 95%